Soploon: A virtual assistant to help teachers to detect object‐oriented errors in students’ source codes - Vallejos, Sebastián; Berdun, Luis S.; Armentano, Marcelo G.; Soria, Álvaro; Teyseyre, Alfredo R. (Computer applications in engineering education, 2018)
When checking students’ source codes, teachers tend to overlook some errors. This work introduces Soploon, a tool that automatically detects novice programmer errors. By using this tool, teachers can reduce the number of overlooked errors. Thus, students receive a more complete and exhaustive feedback about their errors and misconceptions.